2002
DOI: 10.1097/00043764-200202000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Deep Body Core Temperatures in Industrial Workers Under Thermal Stress

Abstract: To date, no field study has continuously monitored the deep body core temperatures of industrial workers. A program to continuously measure deep body core temperatures in 36 industrial workers working 10-, 12-, and 12.5-hour day and nightshifts in a hot, deep, underground mine in the Tropics was conducted. No heat illness occurred in these workers during the study. Miniaturized radio-transponders ("pills") taken orally were used to measure temperature during the transit time in the gastrointestinal tract. Comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(51 citation statements)
references
References 7 publications
3
48
0
Order By: Relevance
“…Working in hot environments, without being adequately acclimated or cooled increases a worker's heat load or thermal stress 3) . When this happens, the build up of heat can impair worker performance, increase accident risk and cause illness or even death.…”
Section: Introductionmentioning
confidence: 99%
“…Working in hot environments, without being adequately acclimated or cooled increases a worker's heat load or thermal stress 3) . When this happens, the build up of heat can impair worker performance, increase accident risk and cause illness or even death.…”
Section: Introductionmentioning
confidence: 99%
“…5, might indicate the limit of one's ability to withstand heat exposure. Studies have indicated that by self-regulating the pace of work the workers could maintain a useful level of workload even under thermally stressful conditions 39,40) .…”
Section: Discussionmentioning
confidence: 99%
“…As these industrial sites tend to be located in remote areas exposed to hot and sometimes humid conditions, the exposure of more personnel to extreme environmental conditions is inevitable. For example, miners have experienced WBGT exposures of 29.1°C to 31.5°C [10,11] and a Basic Effective Temperature ranging between 26.6°C and 29.4°C [12]. Within the mining industry, particularly underground mining, the geothermal gradient contributes to ambient heat.…”
Section: Ambient Working Environmentmentioning
confidence: 99%
“…These measurements could be a misrepresentation as a critical core temperature could have already been reached. It has been previously shown that modifications to work practices begin to occur as ambient conditions increase [11], reducing the effectiveness of this index.…”
Section: Predicted 4 Hour Sweat Rate (P 4 Sr) -Developed By Mcardle Amentioning
confidence: 99%